INVESTIGATION ON THE USE OF MICROPILES FOR SUBSTITUTION OF DEFECTED PILES BY THE FINITE ELEMENT METHOD (Journal of Engineering, 2010)
Micropiles are small diameter, cast in – place or grouted piles with steel pipes of (50 to 300 mm) diameters and driven by boring machine. Despite their small wall thickness, high bearing capacity of micropiles provides both axial and pullout resistance.nThis paper is directed to study the behavior of micropiles under static and dynamic loading conditions using the finite element method. The program OpenSees is used in the analysis, it is open – source program, provides information about the software architecture, access to the source code, and the development process. The program is based on the basic commands, which are written in Tcl (pronounced, "tickle"; tool command language). A model for groups of laterally loaded pipe piles in sand was adopted to study the effect of defects on their lateral performance. The geometric arrangement consisted of group series of 2, 4 and 6 equally spaced piles. Eight node brick elements are used to model the pile and the surrounding soil. It was concluded that the deflection of laterally loaded piles decreases when inserting steel micropiles beside the defect pile at two opposite directions. The increase in the group deflection is greater when the defected pile is modeled in the front row.